2019
DOI: 10.21037/qims.2018.09.17
|View full text |Cite
|
Sign up to set email alerts
|

Imitating human soft tissue on basis of a dual-material 3D print using a support-filled metamaterial to provide bimanual haptic for a hand surgery training system

Abstract: Background: Currently, it is common practice to use three-dimensional (3D) printers not only for rapid prototyping in the industry, but also in the medical area to create medical applications for training inexperienced surgeons. In a clinical training simulator for minimally invasive bone drilling to fix hand fractures with Kirschner-wires (K-wires), a 3D-printed hand phantom must not only be geometrically but also haptically correct. Due to a limited view during an operation, surgeons need to perfectly locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…By reducing the amount of TP in the inner volume through SUP, an object becomes significantly softer. This makes it possible to soften the raw TP material to reproduce a realistic replica of human hand soft tissue (17). The CF design convinced with its elasticity and softened the TP material.…”
Section: Soft Tissue Imitation and Previous Workmentioning
confidence: 98%
See 1 more Smart Citation
“…By reducing the amount of TP in the inner volume through SUP, an object becomes significantly softer. This makes it possible to soften the raw TP material to reproduce a realistic replica of human hand soft tissue (17). The CF design convinced with its elasticity and softened the TP material.…”
Section: Soft Tissue Imitation and Previous Workmentioning
confidence: 98%
“…This corresponds to a value less than five on the shore A scale (16). Thus, in previous work a support-material-filled (supportmaterial, SUP) metamaterial to soften raw TP and imitate human soft tissue with its haptic and elastic properties was introduced (17). Metamaterials in 3D printing allow to change the haptic features assembling small-scaled structural components (18)(19)(20).…”
Section: Soft Tissue Imitation and Previous Workmentioning
confidence: 99%
“…In the remaining two original studies researchers reported their experiences of developing a realistic 3D printed hand phantom for surgery training purpose, and a multi-purpose breast phantom suitable for multi-modality imaging examinations (27,28). Maier and colleagues provided a very detailed approach of creating 3D printed hand model with haptic properties (27). Their design was based on using the metamaterial filled with blowy support material.…”
mentioning
confidence: 99%
“…An increasing trend in research and publications have been observed recently in the journal of Quantitative Imaging in Medicine and Surgery (QIMS), especially in the 2019 January special issue with a focus on 3D printing in medicine. In that special issue, a number of publications (original studies, technical notes and review articles) were contributed by researchers from different countries with expertise in different fields highlighting the importance of 3D printing in medical applications (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). In addition to these applications, a recent paper in this issue of QIMS presents another new research direction of using personalized 3D printed coronary artery models for simulation of coronary stenting procedure (14).…”
mentioning
confidence: 99%